ASC annual report 2010/2011 - Appendix 1: ASC financial statement - Australian Sports Foundation financial statements (Annual report Australian Sports Commission, 2011)
The report assesses the ASC`s performance against the accountability framework agreed with the Australian Government, and highlights the success of its programs.